Reynolds stress constrained large eddy simulation of separation flows in a U-duct - Quanyong Xu; Yantao Yang (Propulsion and Power Research, 2014)
This paper presents Reynolds stress constrained large eddy simulation (RSC-LES) method applied to a U-duct flow. Different from traditional Reynolds-averaged Navier-Stokes/detached eddy simulation (RANS/DES) hybrid method (including DES method), the RSC-LES method solves the LES equations in the whole computation domain with the near-wall regions being constrained by a prescribed Reynolds stress. By doing so it is possible to overcome the log-law mismatch (LLM) problem in hybrid method. The RSC-LES results show better agreement with experiment result. Compared with RANS and DES, RSC-LES gives more accurate pressure coefficients and friction coefficients on the wall, because the RSC-LES method captures the separation point and reattachment point on the inner wall. The computation results show that the RSC-LES method has the potential to solve the log-law mismatch problem of RANS/DES hybrid method and predict complex phenomena of internal flow field.